‘No Sense of Reality’: George A. Drew’s Anti-Communist Tour of the USSR and the Campaign for Coalition Government in Ontario, 1937 - Niergarth, Kirk (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
In 1936 George Drew, future Premier of Ontario, was greatly concerned that a false and very dangerous impression of the Russian experiment in government was being spread in Ontario. So he traveled to Russia in 1937 where he confirmed his preconceived ideas with first-hand observation. For him, toleration of domestic communism could lead either to the horrors of Stalin’s USSR or to the fascism of Hitler or Mussolini. Canada’s best option, he felt, was to follow Britain in ending partisan politics and establishing a “National Government.” Thus, in the 1930s, he worked, unsuccessfully, to create coalition governments in Toronto and Ottawa. This article concludes that the lens through which Drew viewed the USSR can be reversed to gain insight into the Canadian political culture of which he was a part. The right-wing solutions that Drew advocated were conveyed to the public through international comparison and analogy based on Drew’s eye-witness account of his European tour.